Poczucie własnej wartości oraz wartości własnego ciała u osób ćwiczących regularnie na siłowni – wyniki badań pilotażowych = Self-esteem and the value of body in people who exercise regularly at the gym - the results of pilot studies - Ziemianek, Piotr; Jendrysik, Krzysztof; Horodecki, Mikołaj; Knapik, Andrzej (Journal of Education, Health and Sport, 2015)
Ziemianek Piotr, Jendrysik Krzysztof, Horodecki Mikołaj, Knapik Andrzej. Poczucie własnej wartości oraz wartości własnego ciała u osób ćwiczących regularnie na siłowni – wyniki badań pilotażowych = Self-esteem and the value of body in people who exercise regularly at the gym - the results of pilot studies. Journal of Education, Health and Sport. 2015;5(11):629-638. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35712 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A629-638 http://pbn.nauka.gov.pl/works/684942 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Ziemianek Piotr, Jendrysik Krzysztof, Horodecki Mikołaj, Knapik Andrzej. Poczucie własnej wartości oraz wartości własnego ciała u osób ćwiczących regularnie na siłowni – wyniki badań pilotażowych. Quality in Sport. 2015;1(3):61-69. eISSN 2450-3118. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. Piotr Ziemianek, Krzysztof Jendrysik, Mikołaj Horodecki Wydział Nauk o Zdrowiu, Śląski Uniwersytet Medyczny w Katowicach, SKN przy Zakładzie Adaptowanej Aktywności Fizycznej i Sportu Andrzej Knapik Wydział Nauk o Zdrowiu, Śląski Uniwersytet Medyczny w Katowicach, Zakład Adaptowanej Aktywności Fizycznej i Sportu Poczucie własnej wartości oraz wartości własnego ciała u osób ćwiczących regularnie na siłowni – wyniki badań pilotażowych Self-esteem and the value of body in people who exercise regularly at the gym - the results of pilot studies Streszczenie Wstęp. Ćwiczenie na siłowni staje się coraz bardziej popularne, zarówno wśród kobiet, jak i wśród mężczyzn. Regularne treningi, poza zmianami morfologicznymi oraz funkcjonalnymi mogą mieć wpływ na zmiany pewnych aspektów psychologicznych, szczególnie dotyczących poczucia własnej wartości oraz postrzegania własnego ciała. Cel. Postanowiono określić poziom poczucia własnej wartości oraz poczucia wartości własnego ciała u osób ćwiczących na siłowni. Ponadto celem badań było zbadanie wzajemnych zależności między tymi rodzajami samooceny oraz ocena wpływu wieku i stażu treningowego na ich poziom u kobiet i u mężczyzn. Materiał i metody. Zbadano 73 osoby regularnie ćwiczące na siłowni: 23 kobiety i 50 mężczyzn. Narzędziem badawczym był kwestionariusz, zawierający Skalę Samooceny Rosenberga (SES) oraz Skalę Poczucia Wartości Własnego Ciała (BES). Wyniki. Zarówno kobiety, jak i mężczyźni ocenili poczucie własnej wartości na poziomie 59% możliwych do uzyskania punktów. Również poczucie wartości własnego ciała i jego składowe były powyżej połowy możliwych do uzyskania punktów. Nie znaleziono korelacji poczucia własnej wartości z poczuciem wartości własnego ciała. Odnotowano silne wzajemne korelacje między składowymi skali BES. Wśród kobiet odnotowano korelację wieku z wynikami SES. Wnioski. Osoby ćwiczące na siłowni mają dobry poziom globalnej samooceny oraz poczucia wartości własnego ciała. Badane rodzaje samooceny nie są wzajemnymi korelatami. Aspekty poczucia wartości własnego ciała są ze sobą skorelowane. Wśród kobiet wiek wpływa dodatnio na poczucie własnej wartości. Abstract Admission. Exercise at the gym has become increasingly popular, both among women and among men. Regular workouts besides morphological and functional changes may affect the amendment of certain psychological aspects, particularly concerning self-esteem and perception of their own body. Objective. It was decided to determine the level of self-esteem and a sense of one's own body in people exercising in the gym. Moreover, the aim of the study was to examine the interrelationships between these types of self-assessment and the assessment of the effects of age and training experience to their level in men and women. Materials and methods. We examined 73 people regularly exercising at the gym: 23 women and 50 men. The research tool was a questionnaire containing the Rosenberg Self-Assessment Scale (SES) and the scale of self-esteem own body (BES). Results. Both women and men assessed self-esteem at the level of 59% of possible points. Also, a sense of one's own body and its components were more than half of the possible points. No correlation was found self-esteem with a sense of your own body. There has been strong correlations between the components of the scale BES. Among women aged noted a correlation with the results of the SES. Conclusions. People exercising at the gym have a good level of global self-esteem and a sense of your own body. Tested types of self-esteem are not mutually correlates. Aspects of self-esteem own body are correlated. Among women age has a positive effect on self-esteem. Słowa kluczowe: ćwiczenie na siłowni, samoocena, poczucie wartości własnego ciała. Key words: exercising at a gym, self-esteem, sense of one’s own body.